Limit and relationship: think the contact from the philosophy of Gilbert Simondon - Bardet, Marie (Revista de Filosofía, 2019)
This text proposes to read the work of Gilbert Simondon from a question for skin and contact. Its conceptualization of the limit and the relationship in L’Individuation à la lumière des notions de forme et d’information allows conceptual lines to be drawn to think about the skin and the contact, and a dialogue to be establish between his philosophy and corporal and artistic practices from somatics and dance fields. To read Simondon’s philosophy in dialogue with sensitive experiences allows to understand some of the central concepts of his philosophical work and original conceptualizations that are elaborated in the crossing.